2013
DOI: 10.1590/s0104-11692013000700008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of elderly persons' functionality and care needs

Abstract: Objective: To evaluate the elderly persons' functionality, based on the International Classification of Functionality. Methods: a cross-sectional, descriptive study; a stratified random sample of 903 elderly persons; a confidence level of 95%; and a margin of error of 2.5%. Questionnaire based on the International Classification of Functionality; data was collected based on structured interviews undertaken by health professionals in the health centers in the Alentejo region of Portugal. Results: 30.7% of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
4
14
0
5
Order By: Relevance
“…Also noteworthy is the higher number of individuals with illiteracy, which is particularly prevalent in women. Regarding education level, our data showed that 29.6% of the participants stated that they could neither read nor write; a very similar result was found in (51). In our study, this population was predominantly female (57.8%) and in the age groups of 75-84 and 85 years and over.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Also noteworthy is the higher number of individuals with illiteracy, which is particularly prevalent in women. Regarding education level, our data showed that 29.6% of the participants stated that they could neither read nor write; a very similar result was found in (51). In our study, this population was predominantly female (57.8%) and in the age groups of 75-84 and 85 years and over.…”
Section: Discussionsupporting
confidence: 79%
“…This result is likely associated with a greater predisposition of women to physical and mental problems compared with men, indicating a greater difficulty in accepting aging and resulting in a more negative QOL assessment, as has been suggested in several studies (22), (52), (67), (68). Other studies report that long-lived women exhibit more limitations and a greater loss of functional capacity as a result of a higher prevalence of chronic diseases, with negative impacts on the QOL in both of the mentioned domains (69), (51). Regarding both genders, QOL varied negatively with increasing age (i.e., a negative association was observed in all domains), which may be related to an increased overall burden of disease as a person ages, thus resulting in a decline in health (70).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, human aging is a slow and inevitable process, leading to various morphological, functional, biochemical and psychological changes that may contribute to increasing vulnerability to and the incidence of pathological processes in the body. In most cases, elderly patients experiencing worsening health conditions (e.g., cardiac, respiratory or cerebrovascular problems, urinary infections, diabetes and fall-related injuries) usually use the emergency department of the Hospital of BAR, according to several international studies 4,[7][8][9] .…”
mentioning
confidence: 99%
“…Schooling had no statistical significance in this study, even though it was associated with self-care agency in other studies (1)(2)5,8) , which showed that individuals in preoperative CABG surgery with little schooling had a knowledge deficit on their own health condition and treatment (6) . The unfavorable socioeconomic scenario, characterized by low schooling, poor income, and aging along with comorbidities creates obstacles to improved health condition (23) . However, one can observe in the researched sample an ability to deal with such adversities, called self-care agency.…”
Section: Discussionmentioning
confidence: 99%